The fifty-ninth Congress, its organization, personnel, and acts - Thompson, R. C. (My University, 1908)
Introduction: The Fifty-ninth Congress began with a special session of the Senate on March 4, 1905, immediately after the adjournment of the Fifty-Eighth Congress. It is customary for the outgoing President to issue a call for a special session of the Senate to assemble on the day of the inauguration of the President.
Citation: Thompson, R. C. The fifty-ninth Congress, its organization, personnel, and acts. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Congress; United States; Political Science; Senate; Graduating theses; Senior theses; Theses